Analysis of Physical Violence Practices as a Violation of the Right to Security in Legal and Human Rights Perspectives: Analisis Praktik Kekerasan Fisik Sebagai Pelanggaran Hak Atas Rasa Aman dalam Perspektif Hukum dan HAM - Risman Setiawan; Hardianto (Yayasan Cerdas Pedia Indonesia, 2025)
This research examines assault and violations of the right to personal security from the perspective of national law and human rights principles, focusing on practices of physical violence. The violation of the right to personal security represents a concrete manifestation of assault that not only causes physical harm to victims but also entails psychological and social consequences. Employing a normative-juridical approach with legal document analysis methodology including statutes, court decisions, and international human rights instruments this study demonstrates that physical violence often occurs due to weak law enforcement, inadequate victim protection, and insufficient understanding of human rights principles by law enforcement authorities. The research emphasizes the critical importance of harmonizing national criminal law with international human rights standards to ensure effective protection of individuals from assault and violence. This comprehensive protection framework must integrate criminal law, human rights law, social protection, public education, and technological mechanisms to secure the fundamental right to personal security guaranteed by both the Constitution and international law.